Efectos de la Inoculación con Azospirillum brasiliense en la producción de fresa (Fragaria vesca)” - Vera Vera, Julio César (2022)
Strawberry plantations have become a profitable business for different national producers, since it is a product that is sold in different national markets and abroad. Therefore, given the importance of the crop, it is important to analyze inoculants or organic fertilizers that generate advantages and benefits in strawberry plantations, because in the update there is the use of agrochemicals that improve the environment and the strawberry fruit. The objective of the research is to determine the effects of inoculation with Azospirillum brasiliense on strawberry production. The methodology used consisted in the study was made up of a qualitative approach, non-experimental design; while the types of research were descriptive and documentary. In addition, the inductive method was used for the analysis of particular situations on the phenomenon of study and the technique used was content analysis, which allowed establishing the following results: the inoculation of Azospirullum brasilense in the strawberry crop is an effective alternative to increase production, reduce the percentage of rotten fruits, greater root growth, reduce the use of agrochemicals, absorb more water and nutrients from the soil, increase agricultural yield. In conclusion, the application of the inoculation method allows the development of plants with significant yields, which meet the needs of farmers or producers and preserve the environment.